Implementation of the Child Protection Law in Handling Cases of Violence Against Children in Indonesia - Fisabil, Kintan; Putri, Dinda Aulia; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2025)
Family members who commit violence against each other are called domestic violence (KDRT). This form of violence can be physical, psychological, sexual or economic. Domestic violence often occurs in intimate relationships, but can also involve other family members, such as children or parents. One of the most common cases is violence against children, which can be found in various places throughout Indonesia's provinces. This is very paradoxical because parents are supposed to provide sincere love, guidance and education to children, who are supposed to be the next generation. The family, which should be a safe and comfortable place, actually creates fear for children. Children who experience physical, verbal, emotional, mental, or sexual abuse experience symptoms of mental disorders that can interfere with development and social interactions, according to research. To implement the Child Protection Law, the government, society and various parties must work together to create a positive environment that supports children's development. With the right steps, it is hoped that cases of violence against children can be minimized and victims receive the necessary protection.